Design and selection of flotation collectors for zinc oxide minerals based on bond valence model. (1st January 2021) - Zhao, Liang; Liu, Wengang; Duan, Hao; Wang, Xinyang; Fang, Ping; Liu, Wenbao; Zhou, Xiaotong; Shen, Yanbai
Graphical abstract: Highlights: The correlation between stability constants of Zn(II) complexes and bonding strength of ligands is established. The stability analysis of Zn(II)-polar group complex is investigated by DFT computational method. The synergistic effect mechanism of different groups was investigated. Flotation performances of hemimorphite with DGL and LSA are compared. The polar groups of LSA bond with Zn site on the hemimorphite surface formation of the seven-membered structure. Abstract: Based on the bond valence model and density functional theory (DFT), the correlation between the bonding strengths of groups and complex stability constants is established and adopted to design flotation collectors. Lauric acid (LA), N-laurylaminoacetic acid (LAA), N-Dodecanoylglycine (DGL), and N-Lauroylsarcosine (LSA) were used to verify the feasibility of design approach. Micro-flotation tests show that LAA and LSA exhibit better flotation ability than LA and DGL toward hemimorphite. However, the quartz can be collected by LAA due to the highly reactive imine groups, which means it can adsorb on the mineral surface through physical adsorption rather than the chemisorption. Fourier transform IR spectroscopy (FTIR) analysis shows that DGL and LSA can adsorb on hemimorphite surface through chemisorption. X-ray photoelectron spectroscopy (XPS) analysis reveals that the reaction is generated between carboxyl and amide groups and Zn site on the hemimorphite surface, forming seven-membered structure as the DFT simulation shown.